Experimental and Finite Element Studies on Man-Rifle Reaction Force - Cyprian SUCHOCKI; Janusz EWERTOWSKI (Problemy Mechatroniki)
The study concerns a man-weapon interaction during a gunshot. The recoil force measurements obtained for the Kalashnikov automatic rifle are presented and analyzed. The influence of shooter’s mass, height and position is described. The breech pressure and projectile velocity data are presented as well. In addition, a finite element (FE) model of the shooter-rifle system is developed in order to qualitatively assess the quantities which could not be determined experimentally, i.e. the stress, strain and displacement fields which are generated in the human body due to the rifle recoil. Several conclusions are drawn that allow for better understanding of the recoil phenomenon and can be useful from the weapon designer’s point of view.